Positive Association of Leptin and Artery Calcification of Lower Extremity in Patients With Type 2 Diabetes Mellitus: A Pilot Study - Chai, SanBao; Chen, Yao; Xin, SiXu; Yuan, Ning; Liu, YuFang; Sun, JianBin; Meng, XiangYu; Qi, YongFen (Frontiers in Endocrinology, 2021)
Objective: We aimed to explore the role and possible mechanism of leptin in lower-extremity artery calcification in patients with type 2 diabetes mellitus (T2DM). Methods: We recruited 59 male patients with T2DM and 39 non-diabetic male participants. All participants underwent computed tomography scan of lower-extremity arteries. The calcification scores (CSs) were analyzed by standardized software. Plasma leptin level was determined by radioimmunoassay kits. Human vascular smooth muscle cells (VSMCs) calcification model was established by beta-glycerophosphate and calcium chlorideinduction. Calcium deposition and mineralization were measured by the o-cresolphthalein complexone method and Alizarin Red staining. The mRNA expression of bone morphogenic protein 2 (BMP2), runt-related transcription factor 2 (Runx2), osteocalcin (OCN) and osteopontin (OPN) was determined by quantitative RT-PCR. The protein levels of BMP2, Runx2, α-smooth muscle actin (α-SMA) and (p)-Akt was determined by Western-blot analysis, and α-SMA was also measured by immunofluorescence analysis. Results: Compared with controls, patients with T2DM showed higher median calcification score in lower-extremity artery [286.50 (IQR 83.41, 1082.00) vs 68.66 (3.41, 141.30), p<0.01]. Plasma leptin level was higher in patients with calcification score ≥300 than ≥100 (252.67±98.57 vs 189.38±44.19 pg/ml, p<0.05). Compared with calcification medium, intracellular calcium content was significantly increased in VSMCs treated by leptin (200, 400 and 800 ng/ml) combined with calcification medium [11.99±3.63, 15.18±4.55, and 24.14±5.85 mg/ml, respectively, vs 7.27±1.54 mg/ml, all p<0.01]. Compared with calcification medium, Alizarin Red staining showed calcium disposition was more obvious, and the mRNA level of BMP2, Runx2 and OCN was significantly increased, and immunofluorescence and Western blot analysis showed that the expression of α-SMA was downregulated in VSMCs treated by leptin (400 ng/ml) combined with calcification medium, respectively. Compared with calcification medium, the protein level of BMP2 and Runx2 was upregulated in VSMCs treated by leptin (400 ng/ml) combined with calcification medium. Moreover, blocking PI3K/Akt signaling pathway can decrease the protein expression of BMP2 and Runx2 in VSMCs treated by leptin (400 ng/ml) combined with calcification medium. Conclusions: Leptin promoted lower-extremity artery calcification of T2DM by upregulating the expression of BMP2 and Runx2, and regulating phenotypic switch of VSMCs via PI3K/Akt signaling pathway.